Istinto di morte e conoscenza, 40 anni dopo. Roma, 2 luglio 2010. Festa Democratica - Festa dell’Unità - Vari, Autori (Il sogno della farfalla, 2011)
A presentation of the new edition of Death Instinct and knowledge took place on the 2nd July 2010 at the Festival of the “Unità” at the Terme of Caracalla, in Rome, in the very location where in September 1980, Massimo Fagioli and the Collective Analysis were invited by the former Italian Communist Party. The coincidence of these two events, 30 years later, offered the speakers a starting point for the narration of the history as well as the topicality of this book.